Preservation solution Custodiol containing human alpha-1-antitrypsin improves graft recovery after prolonged cold ischemic storage in a rat model of heart transplantation - Korkmaz-İçöz, Sevil; Abulizi-Tursun, Sophia; Li, Kunsheng; Korkmaz, Brice; Georgevici, Adrian-Iustin; Sayour, Alex Ali; Loganathan, Sivakkanan; Canoglu, Hansa; Karck, Matthias; Szabó, Gábor (Frontiers in immunology, 2023)
IntroductionThe shortage of available donor hearts and the risk of ischemia/reperfusion injury restrict heart transplantation (HTX). Alpha-1-antitrypsin (AAT), a well-characterized inhibitor of neutrophil serine protease, is used in augmentation therapy to treat emphysema due to severe AAT deficiency. Evidence demonstrates its additional anti-inflammatory and tissue-protective effects. We hypothesized that adding human AAT in a preservation solution reduces graft dysfunction in a rat model of HTX following extended cold ischemic storage.MethodsThe hearts from isogenic Lewis donor rats were explanted, stored for either 1h or 5h in cold Custodiol supplemented with either vehicle (1h ischemia, n=7 or 5h ischemia, n=7 groups) or 1 mg/ml AAT (1h ischemia+AAT, n=7 or 5h ischemia+AAT, n=9 groups) before heterotopic HTX. Left-ventricular (LV) graft function was evaluated in vivo 1.5h after HTX. Immunohistochemical detection of myeloperoxydase (MPO) was performed in myocardial tissue and expression of 88 gene quantified with PCR was analyzed both statistical and with machine-learning methods.ResultsAfter HTX, LV systolic function (dP/dtmax 1h ischemia+AAT 4197 ± 256 vs 1h ischemia 3123 ± 110; 5h ischemia+AAT 2858 ± 154 vs 5h ischemia 1843 ± 104mmHg/s, p<0.05) and diastolic function (dP/dtmin 5h ischemia+AAT 1516 ± 68 vs 5h ischemia 1095 ± 67mmHg/s, p<0.05) at an intraventricular volume of 90µl were improved in the AAT groups compared with the corresponding vehicle groups. In addition, the rate pressure product (1h ischemia+AAT 53 ± 4 vs 1h ischemia 26 ± 1; 5h ischemia+AAT 37 ± 3 vs 5h ischemia 21 ± 1mmHg*beats/min at an intraventricular volume of 90µl; p<0.05) was increased in the AAT groups compared with the corresponding vehicle groups. Moreover, the 5h ischemia+AAT hearts exhibited a significant reduction in MPO-positive cell infiltration in comparison to the 5h ischemia group. Our computational analysis shows that ischemia+AAT network displays higher homogeneity, more positive and fewer negative gene correlations than the ischemia+placebo network.DiscussionWe provided experimental evidence that AAT protects cardiac grafts from prolonged cold ischemia during HTX in rats.
Gesehen am 24.07.2023